The Role of the Family in Shaping the Character of Broken Home Children in Wanath Hamlet, Leihitu District, Central Maluku Regency - Wa Ramla; Aisa Abas; Titus Gaite (CV. Rayyan Dwi Bharata, 2023)
This research is a qualitative descriptive study that aims to determine the role of the family in shaping the character of broken home children in Wanath Hamlet, Kec. Leihitu Kab. Central Moluccas. This research was conducted in Wanath Hamlet, Leihitu District, Central Maluku Regency. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved. Based on the results of interviews conducted by researchers, it was revealed that most of the children who were in a broken home family situation had negative characters, one of which was being a child who liked to fight when ordered, did not listen when his parents advised him, but some of them who like to help their parents when their parents are sick. The activities of the children in Wanath Waisane Hamlet are not far from helping their parents at home, both boys and girls. If men help by adding water and for women cooking and cleaning the house. , in this case it becomes a separate task for the family in shaping the character of the child to be even better. Therefore, the family's efforts, in this case the parents of broken home children, by giving advice to their children and also applying rules that can make children their children get better or even limit their children's association. In addition to the efforts that have been made by the family, of course there must be obstacles to lack of communication, cell phones and also environmental factors of friendship, for example, but the rules and advice that are carried out by parents do not rule out the possibility of being a supporting factor for the role of parents of broken home kids.